A qualitative assessment of adolescent perspectives on patient education in the outpatient setting - Nicole Meyers; Michelle Kaminski; Samuel Master; Marina Catallozzi; Suzanne Friedman (Elsevier, 2023)
Objective: To explore adolescent perspectives on the content and delivery of anticipatory guidance (AG), both during and after outpatient visits, in order to develop targeted resources and educational material for adolescent patients. Methods: Semi-structured phone interviews among patients ages 12 to 21 seen between May-July 2021 at four outpatient sites of NewYork Presbyterian Hospital were recorded, transcribed and analyzed using thematic analysis. Content domains included attitudes toward and preferences around AG, discharge instructions and patient education resources. Results: Twenty-eight of 156 recruited patients completed interviews; 52% received an After Visit Summary (AVS); of the 48% who did not receive it, half of them expressed interest in receiving one. Themes included positive perceptions of the AVS, patient-physician communication, multimodal delivery of educational materials, and critical discussion topics such as mental health and nutrition. Conclusion: Adolescents value the AVS and prefer multimodal materials and topics that are specifically geared towards them, rather than their caregivers. Innovation: This study is the first to explore adolescent perspectives on AG and after-visit informational materials. These findings may help more effectively reach, educate and engage adolescent patients in the primary care setting by guiding the focused development of patient-centered instructions and resources.